1H NMR analysis of the aqueous-alcoholic mixtures, prepared with drinking water of south-eastern region of Ukraine - Kuzmin, Oleg; Topol’nik, Vera; Sujkov, Sergey (My University, 2013)
The mechanisms of transformation of protons of ethanol and drinking-water are studied in the process of creation of aqueous-alcoholic mixtures.
Keywords: 1H ЯМР спектроскопія; 1H NMR spectroscopy; водно-спиртова суміш; aqueous-alcoholic mixture; етанол; ethanol; кафедра технології ресторанної і аюрведичної продукції